Social psychology : social influence, attitude change, group processes, and prejudice - Collins, Barry E. (Reading, Massachusetts : Addision-Wesley Publishing Company, 1970)
I do feel that attitudes are correlated with behavior; but I don't think that there was a diagnostic instrument available in the autumn of 1964 which could have predicted that I would be writing a prefix to an introductory text in social psychology in the autumn of 1969. I started the project when Tom Williamson asked if I would be interested in writing four chapters on attitude change as a part of a collaborative effort. Since I was then deeply immersed in writing part of a graduate-level text on attitude change with Norman Miller and Charles Kiesler (Attitude Change: A Critical Analysis of Theoretical Approaches), my part of the collaboration was a natural extension of what I was doing; so I agreed. But that project fell through in the spring of 1967. Should I abandon what I had written, or should I undertake to write an introductory text on my own? I wrote Harold Guetzkow, with whom I had collaborated on a graduate-level text on group behavior, and he graciously gave me permission to beg, borrow, and steal whatever material I might need from that source, if I should decide to write a more general social-psychology textbook. Richard Ashmore agreed to write two chapters on prejudice and prejudice reduction. This material, along with the material on attitude change that I had already pre-pared, did seem to provide a reasonable foundation for a textbook. But I still wondered if there was need for another textbook in social psychology; the middle 1960's had seen a rapid growth in the number and quality of general social-psychological textbooks. For several reasons, I decided to add one more.
Social Influence and Conformity -- Social Attitudes -- Group Processes -- Prejudice: Causes and Cures.
Includes bibliographical references and index.
Keywords: SOCIAL PSYCHOLOGY